(untitled) (diségno, 2019)
In recent years I have found myself reflecting more and more often on the relationship between the geometry of representation and cartography, trying to find a link between these two subjects that could take into account my two paths of life and of research, developed along parallel lines, apparently without points of contact. It is clear that this reflection did not refer to the need of giving meaning to my personal choices, something that can only be of interest to myself, but rather of understanding if there were, and in what terms, a historical, epistemological link between these two disciplines with very indistinct boundaries. (read more)